ANKZF1 helps to eliminate stress-damaged mitochondria by LC3-mediated mitophagy - Mudassar Ali; Anjali; Koyeli Mapa (Cell Death Discovery)
Abstract Mitochondria, the double membrane-bound organelles of endosymbiotic origin, are crucial centers for cellular energy production and several essential metabolic pathways. Recent studies reveal that mitochondria become dysfunctional following numerous cellular stresses, and during pathologies, demanding an extensive investigation of mitochondrial turnover mechanisms. Apart from the specific response pathways to tackle different stresses, mitophagy, or degradation of mitochondria by autophagy, is a critical quality control mechanism that clears irreversibly damaged mitochondria. Mitophagy is majorly executed either by receptor-mediated or PINK1-Parkin-dependent pathways. Here, we show that the human orthologue of yeast Vms1, ANKZF1, participates in PINK1-Parkin-mediated mitophagy. We show that ANKZF1 is extensively recruited to damaged mitochondria along with Parkin during mitochondrial proteotoxic stress induced by the expression of a single misfolded/aggregated protein or during uncoupler-induced membrane depolarization. Importantly, ANKZF1 recruitment to damaged mitochondria is significantly enhanced in the presence of Parkin, and ANKZF1 physically interacts with Parkin and LC3 during mitochondrial proteotoxic or depolarization stress. ANKZF1 harbors six putative LC3-interacting regions (LIRs), LIR4 present at residues 333-336, is particularly important for ANKZF1-LC3 interaction. Furthermore, we show that ANKZF1 knockout cells are compromised in clearing stress-damaged mitochondria by mitophagy, indicating an important role of ANKZF1 in mitochondrial turnover during stress. In summary, we show a new role of ANKZF1 in eliminating the stress-damaged mitochondria, reiterating the mito-protective role of Vms1/ANKZF1 during mitochondrial stresses. PINK1/Parkin signaling leads to polyubiquitination of outer mitochondrial membrane (OMM) proteins on stressed mitochondria. ANKZF1 functions as an adaptor protein, binding to polyubiquitinated OMM proteins via UBA domain and autophagosome receptor LC3 via LIR motif.